2012
DOI: 10.1002/cctc.201200447
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of α,β‐Unsaturated Aldehydes and Ketones using Novel Manganese Oxide and Platinum Supported on Manganese Oxide Octahedral Molecular Sieves as Catalysts

Abstract: The selective hydrogenation of α,β‐unsaturated aldehydes and ketones has been studied using ketoisophorone and cinnamaldehyde as model substrates using manganese oxide octahedral molecular sieve (OMS‐2) based catalysts. For the first time, OMS‐2 has been shown to be an efficient and selective hydrogenation catalyst. High selectivities for either the CC or CO double bond at ≈100 % conversion were achieved by using OMS‐2 and platinum supported on OMS‐2 catalysts. Density functional theory (DFT) calculations sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
64
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 30 publications
6
64
0
2
Order By: Relevance
“…Selective hydrogenation of a,b-unsaturated aldehydes at the carbonyl (C@O) and olefinic (C@C) groups is highly desirable in the fine chemical industry, because most of their products are important intermediates for the synthesis of many chemicals [1]. Cinnamaldehyde (CAL) is a particularly important a,bunsaturated aldehyde, since its partial hydrogenation products are important intermediates in the manufacture of chemicals (particularly perfumes, flavors, and pharmaceuticals) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Selective hydrogenation of a,b-unsaturated aldehydes at the carbonyl (C@O) and olefinic (C@C) groups is highly desirable in the fine chemical industry, because most of their products are important intermediates for the synthesis of many chemicals [1]. Cinnamaldehyde (CAL) is a particularly important a,bunsaturated aldehyde, since its partial hydrogenation products are important intermediates in the manufacture of chemicals (particularly perfumes, flavors, and pharmaceuticals) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the solvent 35 effect is not included explicitly in this system. In our previous work 8 it has already been demonstrated that, the chemistry including the selectivity can be adequately using this approach. From Figure 2, it can be seen that the adsorption energies on both Pt(111) and Pt(211) for KIP are significantly lower than those found for CIN and the adsorption energy for KIP on 50 OMS-2 is comparable with that on the Pt.…”
mentioning
confidence: 98%
“…8 In the case of KIP, 98% selectivity for 65 the selective reduction of the C=C bond occurred resulting in the production of (6R)-2,2,6-trimethylcyclohexane-1,4-dione (levodione) at 100% conversion. OMS-2 was also found to be active for the same hydrogenation and also formed levodione selectively (97%), albeit at a lower reaction rate.…”
mentioning
confidence: 99%
“…The unique advantage of such catalysts is that activity and selectivity can be tuned by controlling the size, shape, and surface species of Pt particles [1,[13][14][15]. In fact, many methods have been developed to enhance the performance of Pt-based catalyst, such as investigating novel support and promoter [15][16][17][18][19]. In our previous works, it was found that graphenesupported Pt catalysts showed high selectivity to COL [13]; and the activity and selectivity of Pt/carbon nanosheets (CNS) catalysts increased with the rise of the graphitization degree of CNS [20].…”
Section: Introductionmentioning
confidence: 99%